The Determinants of Growth in EU Border Regions - Dimitris Kallioras; George Petrakos; Maria Tsiapa; Lefteris Topaloglou (European Regional Science Association (ERSA), 2010)
The abolition of the artificial impediments of cross-border interaction has produced a new EU regional socioeconomic map, releasing dynamics that have influenced significantly the EU socioeconomic space. Especially at the borderlands, a new mix of opportunities and threats has come forth, putting EU border regions in a state of flux. The paper compiles a cross-section empirical econometric model that accounts for growth performance in the 349 EU NUTS III border regions during the period 2000-2006. The findings of the paper suggest that there is a series of inherent and acquired factors (initial conditions) that determine the growth performance in the EU border regions. These factors are both ('traditional') quantitative and qualitative ("soft"), indicating the complexity of border issues. The findings of the econometric investigation have important implications for both theory and policy.
Keywords: R11; R12; 330; determinants of growth; EU border regions; integration; cross border interaction